2015
DOI: 10.1016/j.ccell.2015.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Inherited and Somatic Defects in DDX41 in Myeloid Neoplasms

Abstract: Most cases of adult myeloid neoplasms are routinely assumed to be sporadic. Here, we describe an adult familial acute myeloid leukemia (AML) syndrome caused by germline mutations in the DEAD/H-box helicase gene DDX41. DDX41 was also found to be affected by somatic mutations in sporadic cases of myeloid neoplasms as well as in a biallelic fashion in 50% of patients with germline DDX41 mutations. Moreover, corresponding deletions on 5q35.3 present in 6% of cases led to haploinsufficient DDX41 expression. DDX41 l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

30
432
3
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 379 publications
(473 citation statements)
references
References 42 publications
30
432
3
8
Order By: Relevance
“…Of the eight, three harbored the germline D140Gfs*2 variant, confirming its status as the most common site of mutation in Caucasian populations (Fig. 1, 14 families) [19][20][21]. Two families carried a novel germline M1I mutation which was also seen in subsequent studies, making it the second most frequent germline DDX41 mutation in Caucasian populations (5 families) [20,[22][23][24].…”
Section: Mutation Of Ddx41 In Familial Hematological Malignancies (Fhm)supporting
confidence: 56%
See 4 more Smart Citations
“…Of the eight, three harbored the germline D140Gfs*2 variant, confirming its status as the most common site of mutation in Caucasian populations (Fig. 1, 14 families) [19][20][21]. Two families carried a novel germline M1I mutation which was also seen in subsequent studies, making it the second most frequent germline DDX41 mutation in Caucasian populations (5 families) [20,[22][23][24].…”
Section: Mutation Of Ddx41 In Familial Hematological Malignancies (Fhm)supporting
confidence: 56%
“…In the same study cohort, further screening of both familial and sporadic myeloid malignancies identified a further 10 families or singleton cases carrying the germline D140Gfs*2 mutation, as well as identifying additional germline mutations such as I1396T, F183I, Q52fs and M155I mutations ( Fig. 1) [19]. Somatic DDX41 mutations were frequently observed in myeloid tumors of germline DDX41 mutated individuals.…”
Section: Mutation Of Ddx41 In Familial Hematological Malignancies (Fhm)mentioning
confidence: 94%
See 3 more Smart Citations